Antecedentes y genealogía de la historiografía sobre la Historia Reciente en la Argentina - Débora D’Antonio; Ariel Eidelman (Nuevo mundo - Mundos Nuevos, 2013)
Several academic exchanges have shown different viewpoints as to how the field of study of Argentina’s recent history has been built. While some point out that the research carried out in relation to recent history has been developing since the 80s, others refer the starting to the last decade. In this article, we would like to weigh the unavoidable background we deem essential to develop this specific field of study. The existence of a genealogy extended in time encompasses the recognition of the contributions arising from different Social Sciences fields, in other words, beyond the historical studies that have found a turning point in their development in the last years. We will particularly focus on those debates and discussions on Sociology and Political Sciences that have become immediate background of the historiographic research key points. For such purpose, we will start with some debates that took place between the 60s and 70s in the political and social spheres and that have affected the academic reflection about this period. Additionally, we will mention important works from other intellectual spheres that have been done on the Argentine and Latin American history and we will briefly review the current status of the fields of academics study on Recent History in Argentina.